Batubara Formasi Warukin di daerah Sampit dan sekitarnya, Kalimantan Tengah - Kusnama, Kusnama (Geological Agency, 2008)
http://dx.doi.org/10.17014/ijog.vol3no1.20082The Warukin Formation in Sampit area, occupying the Barito Basin, was conformably deposited on top of the Berai Formation, but unconformably lies on the Tanjung Formation, Undifferentiated Metamorphic Rocks and Sepauk Granitic Rock. The formation consists of sandstone, interbedded claystone-mudstone, conglomerate and intercalations of coal, having Early-Late Miocene in age. Coal of the Warukin Formation at the Sampit area occurs within sandstone and interbedded claystone-mudstone facies. Two main seams, A and B, was deposited within sandstone and interbedded claystone-mudstone facies respectively. Generally, the coal is bright banded with partly dull lithotypes; brownish black in colour and it has a medium to light in weight. Physically, the coal recognized in two seams, is generally banded with brittle to friable in hardness; and has partings of claystone and mudstone. The thickness of the coal deposit ranges from 80 cm to 200 cm. On the basis of calorific value and lithotype, and also ash, moisture, and sulphur contents, the coal includes to subbituminous C - A rank. The coal was deposited in a wet-forest swamp occupied by high plants and shrubs. Â Â